2021
DOI: 10.1021/acs.energyfuels.1c00652
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Self-Aggregation of Porphyrins and Their Influence on Asphaltene Aggregation

Abstract: Despite the studies on asphaltene aggregation throughout few decades, the formation of asphaltene aggregates and subsequent deposition are still the biggest challenges in the oil industry. Especially, the role of porphyrins existing in oil naturally on asphaltene aggregation is not completely understood due to asphaltene’s and porphyrin’s special structures. Herein, we investigated the influence of tetraphenylporphyrin (TPP), nickel tetraphenylporphyrin (NiTPP), and vanadium tetraphenylporphyrin (VOTPP) on asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…6,7 However, outside of the biological systems, self-aggregation tendencies and/or selfdestructive effects are well-known in porphyrins. 8,9 It has been approved that porphyrin formulation in a porous structure can remarkably stabilize the structure and inhibit the drawbacks mentioned above.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 However, outside of the biological systems, self-aggregation tendencies and/or selfdestructive effects are well-known in porphyrins. 8,9 It has been approved that porphyrin formulation in a porous structure can remarkably stabilize the structure and inhibit the drawbacks mentioned above.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Porphyrins and their analogues (such as chlorophyll and hemoproteins) are frequently observed in nature, which perform various important biological processes. As a result, they have been enormously investigated in the artificial synthesis and application of porphyrins as attractive materials in different arrays such as drug delivery, medical, electronics, optoelectronics, and photonics. , However, outside of the biological systems, self-aggregation tendencies and/or self-destructive effects are well-known in porphyrins. , It has been approved that porphyrin formulation in a porous structure can remarkably stabilize the structure and inhibit the drawbacks mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that, at concentrations of 5 wt %, most asphaltenes are present in the toluene solution as part of aggregates . A number of studies have shown that vanadyl porphyrins affect the formation of aggregates; , however, it is still not entirely clear due to which interactions this occurs. In another paper, it has been shown that π–π stacking interaction between vanadyl porphyrins and nonpolar aromatic molecules does not lead to the formation of their stable associates.…”
Section: Resultsmentioning
confidence: 99%
“…Vanadyl porphyrins can either promote or inhibit the self-assembly of asphaltene nanoaggregates depending on their size and the presence of peripheral functional groups. 8,34 The degree of such an influence depends on how compact the monomer packing is in the initial asphaltene aggregates. 8 Thus, the formation of asphaltene−resin−paraffin deposits in the presence of metal-porphyrins is a complex all-inclusive problem.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The content of vanadium can reach almost 0.2 wt % and nickel 0.02 wt %, the presence of which in feedstock is a serious challenge for oil refining. , Issues related to their distribution in resin and asphaltene fractions and the impact on the processes of asphaltene aggregation and paraffin crystallization are important for developing an optimal strategy not only for oil refining technologies but also for minimizing the damage associated with the formation of deposits during oil production and transportation. Vanadyl porphyrins can either promote or inhibit the self-assembly of asphaltene nanoaggregates depending on their size and the presence of peripheral functional groups. , The degree of such an influence depends on how compact the monomer packing is in the initial asphaltene aggregates …”
Section: Introductionmentioning
confidence: 99%